Measuring E-Readiness in Implementing LMS Moodle at SMAN 10 Bandung Using the Technology Readiness Index (TRI) Model - Manaf, Khaerul; Hernadi, Mohamad Gani; Subaeki, Beki; Gunawan, Yanyan (JESII: Journal of Elektronik Sistem InformasI, 2024)
Technological advancements encourage the education sector to adopt information technology, including Learning Management Systems (LMS). This study aims to measure the level of technological readiness (e-readiness) for implementing LMS Moodle at SMAN 10 Bandung using the Technology Readiness Index (TRI) model. The TRI method assesses four main dimensions: Optimism, Innovativeness, Discomfort, and Insecurity. The results reveal that SMAN 10 Bandung has a moderate level of readiness, with a total TRI score of 2.92. The Optimism variable received the highest score (0.84), while the Discomfort variable had the lowest score (0.51). Based on these results, SMAN 10 Bandung falls under the Explorers category, characterized by optimistic and innovative attitudes toward technology. Recommendations include providing additional training to reduce discomfort and insecurity when using new technology.